Bond behavior between steel bar and strain-hardening fiber-reinforced cementitious composites under fatigue loading - Li, Qing-Hua; Luo, Ai-Min; Huang, Bo-Tao; Wang, Guo-Zhong; Xu, Shi-Lang (Engineering structures, 2024)
Ultra High Toughness Cementitious Composites (UHTCC), a series of cement-based materials with significant tensile strain-hardening and multi-cracking behaviors, can be applied to enhance the fatigue resistance of reinforced concrete structures. The deterioration of the bond between steel bar and UHTCC caused by fatigue loadings has a significant impact on the mechanical performance of concrete structures. This study investigated the fatigue and post-fatigue monotonic bond behavior between steel rebar and UHTCC for the first time. The results showed that the one-side reduction of UHTCC layer had marginal effect on the monotonic and fatigue bond performance. Notably, the ultimate slip under fatigue loading was much larger than the monotonic envelop at the same stress level. Additionally, a new model was proposed to describe the evolution of fatigue slip. Then, the influence of fatigue loading history on the residual bond performance was investigated. It was found that UHTCC exhibited a lower degradation rate of bond stiffness compared with ordinary concrete, owing to the superior crack resistance. The stress-slip curve of post-fatigue monotonic specimen was predicted by a semi-empirical model. This study laid the groundwork for understanding and modeling the fatigue and post-fatigue monotonic bond behavior between steel rebar and UHTCC, which is useful for applying UHTCC materials in resilient infrastructure. •The fatigue and post-fatigue monotonic bond behavior between steel rebar and UHTCC was investigated for the first time.•The one-side reduction of UHTCC layer had marginal effect on the monotonic and fatigue bond performance.•A new model was proposed to describe the evolution of fatigue slip.•UHTCC exhibited a lower degradation rate of bond stiffness compared with ordinary concrete